Determination of Polar Lipids in Wheat and Oat by a Complementary Approach of Hydrophilic Interaction Liquid Chromatography and Reversed-Phase High-Performance Liquid Chromatography Hyphenated with High-Resolution Mass Spectrometry - Schneider, Svenja; Hammann, Simon; Hayen, Heiko (Journal of Agricultural and Food Chemistry, 2023)
Cereals contain lipids that fulfill important physiological roles and are associated with stress in the plant. However, many of the specific biological roles of lipids are yet unknown. Comprehensive analysis of these polar lipid categories in whole grain wheat and oat, cereals highly relevant also in nutrition, was performed. Hydrophilic interaction liquid chromatography (HILIC) and reversed-phase high-performance liquid chromatography (RP-HPLC) coupled with high-resolution mass spectrometry using electrospray ionization in both positive and negative ionization mode was used. Exploiting the different separation mechanisms, HILIC was used as a screening method for straightforward lipid class assignment and enabled differentiation of isomeric lipid classes, like phosphatidylethanolamine and lyso-N-acylphosphatidylethanolamine, while RP-HPLC facilitated separation of constitutional isomers. In combination with data-dependent MS/MS experiments, 67 lipid species belonging to nine polar lipid classes could be identified. Furthermore, with both ionization modes, fatty acyl chains directly connected to the lipid headgroups could be assigned. This work focused on the four lipid classes N-acylphosphatidylethanolamines, acyl-monogalactosyldiacylglycerols, digalactosyldiacylglycerols, and monogalactosyldiacylglycerols as they were less studied in detail in the past. Applying the complementary approach, the relative lipid species compositions in these lipid classes was investigated in detail.<br
Keywords: cereals lipids phospholipids glycolipids Hydrophilic Interaction Liquid Chromatography (HILIC) reversed-phase HPLC